Navigating in the Midst of Uncertainties: Challenges in Disaster Risk Governance in Mozambique - Koivisto, Jenni (Karlstads universitet, 2018)
Disasters cause heavy losses for societies and may quickly erode any development efforts. Consequently, disaster risk reduction (DRR) is an integral part of development work that should be addressed at multiple levels. Global DRR frameworks, scholars and practitioners all advocate disaster risk governance (DRG) strategies that are multi-stakeholder, polycentric and multisectoral. While various substantive knowledge gaps and questions arising from multiple risks and the crosscutting nature of DRR have been relatively well addressed, uncertainties relating to multiple DRR actors operating and collaborating at different scales have gained less attention in previous studies. This thesis investigates the uncertainties in DRG in Mozambique, a low-income country that regularly faces natural hazards. These hazards often cause heavy loss of life and livelihoods and economic damage. The four articles that together constitute this thesis focus on different sets of uncertainties and factors that have constrained or allowed Mozambique to take major steps in this policy area. By exploring strategic and institutional uncertainties related to stakeholder involvement, coordination and policy disputes, this thesis reveals different challenges and opportunities that affect DRR policymaking in Mozambique. This thesis concludes that Mozambique has managed to take important steps in DRR. However, as a consequence of the different challenges to DRR practice in Mozambique, policymaking can be short-sighted and makes slow progress, thus increasing the disconnect between theory, policies and practice. This thesis thus argues that DRG research and practice need to better take into account power-relations; coordination and capacity issues; and responsibilities and transparency across scales, both in Mozambique and elsewhere.
ISBN: 978-91-7063-875-6 (ISBN) Number Of Volumes: 2018:39 Publication Title: Karlstad University Studies 2018:39
Keywords: G - Mozambique / Moçambique; L - english / inglês; collaboration / colaboração

Facilitators and obstacles to cooperation in international development networks: a network approach - Petersen, Il-haam (Development in Practice, 2016)
This paper draws attention to the value of a network approach for understanding cooperation in international development networks. The approach emphasises the impact of social interaction, and the values, ideas, and behaviours of individuals on the achievement of development goals. Social network analysis is used to analyse the social structure and dynamics of interaction in an aid-funded development network organisation that aimed to develop optometry capacity in Mozambique. The analysis shows the value of combining quantitative and qualitative methods in a complementary way to identify factors facilitating (network consciousness and social skill) and hindering (power dynamics) cooperation.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; collaboration / colaboração

Guião de consulta e participação da sociedade civil e cidadãos no funcionamento dos conselhos consultivos locais - Monjane, Celso; Salimo, Padil (MASC, 2014)
O presente guião é um instrumento que tem em vista dotar as OSC e cidadãos de modo geral, de conhecimentos sobre o funcionamento dos Conselhos Consultivos Locais (CCLs) de maneira a facilitar a sua participação e a alargar as suas intervenções na área de monitoria e advocacia da governação a nível distrital. Estão apresentados neste guião, os elementos que permitem perceber a organização, a estrutura, funções, e responsabilidades dos Conselhos Consultivos Locais, como eles funcionam, as oportunidades existentes para a participação das OSC e cidadãos de um modo geral na articulação com os Conselhos Locais por forma a estimular diálogo e contribuir na melhoria da sua influência na tomada de decisões e na melhorias na prestação de serviços às comunidades a nível dos distritos pelos governos distritais. O guião está estruturado em cinco secções. A primeira secção, apresenta o contexto, objectivos e a metodologia usada na sua elaboração; a segunda secção, procura explicar os principais elementos sobre a participação e consulta comunitárias, as formas de organização das comunidades locais para a participação comunitária, e a importância da participação e consulta comunitária, bem como uma explicação sobre como a consulta e a participação é feita a nível distrital. A terceira secção, apresenta detalhadamente aspectos sobre funcionamento, tarefas e estratégias de trabalho, bem como formas de prestação de contas. A quarta secção, fala sobre os mecanismos de escolha dos membros dos Conselhos Consultivos Locais, número de membros e direitos e deveres que eles possuem. A quinta secção, fornece algumas bases sobre como a sociedade civil e cidadãos podem contribuir para o fortalecimento dos CCLs, bem como, as estratégias para incrementar mecanismos de monitoria e advocacia.
Keywords: *tagged; G - Mozambique / Moçambique; L - portuguese / português; accountability / responsabilização; citizenship & participation / cidadania e participação; collaboration / colaboração; governance / governação; government policy / politica governamental